NILAI MORAL DALAM NOVEL KKN DI DESA PENARI KARYA SIMPLEMAN - Saputri Saputri; Sainil Amral; Harbeng Masni (Universitas Batanghari, 2020)
The purpose of this research is to describe the moral value in the novel KKN di Desa Penari by Simpleman. The results of the research contained a hundred and forty-two expressions. Human relationship with Allah SWT was found as many as forty-one expressions consisting of one expressions of faith in God, four expressions of worshipping Him, ten expressions of patiently accepting His trials, and sixteen expressions of idolatry to God. The human relationship with one another was found to be forty expressions consisting of eight expressions of patient, eight expressions of gratitude, and twenty-three expressions of being grumpy. Human-to-human relationships were found to be sixty-one expressions consisting of eight expressions of fairness, thirty-nine expressions of being helpful, one expression of forgiving, seven expressions of pledge-keeping, four expressions of broken, and two expressions of ignoring others.